WORKSHOP PENGELOLAAN PROGRAM PERKESMAS DENGAN PENYUSUNAN ASUHAN KEPERAWATAN INDIVIDU, KELUARGA DAN KELOMPOK KHUSUS DI PUSKESMAS ADIPALA 1 - Iva Puspaneli Setyaningrum; Aminudin Aminudin (JPS : Jurnal Pengabdian Serulingmas, 2022)
Basic health services are urgently needed to achieve the unreached MDGs targets, the 2030 Sustainable Development Goals (SDGs) and Minimum Service Standards (SPM). The success of basic health services, which are mainly promotive and preventive, will reduce the burden of follow-up services. One of the efforts made by the Puskesmas is the Community Health Care Program (Perkesmas). The family approach is an extension of the Community Health Program including home visits. The Healthy Indonesia Program with a Family Approach (PIS PK) is implemented by integrating individual health efforts (UKP) and community health efforts (UKM) on an ongoing basis. The PIS PK activities carried out cannot be separated from the role of nursing staff. Nursing is the backbone of the health care system and the primary service provider. The role of nurses in implementing programs by managing individual, family and group nursing care in the community. While the results of the survey stated that nurses in documenting family nursing care were only (55.29%). This is related to internal factors and nurse factors. Thus, the Adipala I Health Center seeks to optimize the Community Health Program, including by holding this workshop to improve the ability of nurses in documenting individual, family and special group nursing care. The 2-day workshop method includes lectures and discussions, consisting of 20 nurses, enthusiastic participants in each activity session.